2017
DOI: 10.1186/s11671-017-1925-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Atomic Layer Deposition of High-Density Ni Nanoparticles for Amorphous In-Ga-Zn-O Thin Film Transistor Memory

Abstract: For the first time, the growth of Ni nanoparticles (NPs) was explored by plasma-assisted atomic layer deposition (ALD) technique using NiCp2 and NH3 precursors. Influences of substrate temperature and deposition cycles on ALD Ni NPs were studied by field emission scanning electron microscope and X-ray photoelectron spectroscopy. By optimizing the process parameters, high-density and uniform Ni NPs were achieved in the case of 280 °C substrate temperature and 50 deposition cycles, exhibiting a density of ~1.5 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…The spectrum for Ni2p ( Figure 1 b) was complex because of the significant overlap of the Ni3d and O2p orbitals, resulting in broad peaks with multiple satellite peaks [ 59 , 60 , 61 ]. However, the shape and position of the maxima showed that all the samples under study contain NiO (854.1 eV) and Ni +3 (Ni 2 O 3 and/or Ni 3 O 4 ), or nickel hydroxide—Ni(OH) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum for Ni2p ( Figure 1 b) was complex because of the significant overlap of the Ni3d and O2p orbitals, resulting in broad peaks with multiple satellite peaks [ 59 , 60 , 61 ]. However, the shape and position of the maxima showed that all the samples under study contain NiO (854.1 eV) and Ni +3 (Ni 2 O 3 and/or Ni 3 O 4 ), or nickel hydroxide—Ni(OH) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…By means of plasma ALD, high-density Ni nanocrystals were also successfully obtained using NiCp 2 and NH 3 precursors . Similarly, it is demonstrated that the substrate temperature and deposition cycles significantly affect the areal density and size distribution of Ni nanocrystals.…”
Section: Charge Storage Mediums For Aos Tft Memorymentioning
confidence: 87%
“…This is attributed to some key advantages of metal nanocrystals, including a higher density of states around its Fermi level, stronger coupling with the semiconductor conducting channel, a freer selection of metal work function, and smaller energy perturbation because of the carrier confinement effect . Therefore, various metal nanocrystals have been investigated as charge storage mediums for the Si-based flash memory and AOS TFT memory applications, including Ru, Pt, Ni, and Au nanocrystals, etc. ,,, To obtain metal nanocrystals, different preparation methods can be used, which are roughly classified into colloidal suspension, direct deposition, and ALD. The first one is a chemical wet process, usually being utilized for catalyzers.…”
Section: Charge Storage Mediums For Aos Tft Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Όλες αυτές οι παγίδες δρουν σαν μονοπάτια διαρροής για να διαφύγουν εύκολα τα φορτία [11,14,77,99]. Παρόμοια αποτελέσματα έχουν αναφερθεί για πυκνωτές MOS που περιέχουν είτε μεταλλικούς [109,110,111,112] είτε ημιαγώγιμους [113,114,115,116,117] νανοκρυστάλλους. Για να διερευνηθούν και να διαφοροποιηθούν οι επιδράσεις της διεργασίας ανόπτησης με laser χαμηλής εκπομπής (Low Emission-Excimer Laser Annealing, LEM-ELA) σε νανοκρυστάλλους χρυσού και σε παγίδες στο οξείδιο, υιοθετήθηκε μια ανάλυση βασισμένη στην εκφόρτιση, σύμφωνα με παρόμοιες αναλύσεις που αναφέρονται σε παραπλήσιες δομές [11,14].…”
Section: πειραματικά αποτελέσματα διατήρησης του αποθηκευμένου φορτιού σε μνήμες με νανοκρυστάλλους χρυσού με οξείδιο φραγής Y2o3unclassified